Does TMB impact the effectiveness of TKIs in EGFR-mutant NSCLC? - Cheng, Michael L. (Clin Cancer Res, 2018)
Patients with EGFR-mutant NSCLC achieve variable benefit from targeted therapy, and biomarkers to predict degree of benefit are not in clinical use. EGFR-mutant cancers with high tumor mutational burden demonstrate poorer outcomes on EGFR targeted therapy. Investigation into the mechanisms underlying this intriguing association is needed.